MEMBERDAYAKAN MASYARAKAT MELALUI PROGRAM KKN (KULIAH KERJA NYATA) DALAM MENINGKATKAN KEBERSIHAN DAERAH DI DESA LAWA-LAWA LUO GOMO KECAMATAN GOMO) - Sejahtera Fatemaluo; Tarisman Ndruru; Destriani Hura; Mawati Zalogo; Angelia Fitriani Ndruru; Asaridi Zalukhu; Fajardin Laowo; Fanahatodo Ndruru; Silvester Jessen Duha; Firminus Antusias Duha (Universitas Nias Raya, 2025)
Maintaining cleanliness and environmental health around residential areas is a crucial step in preventing the spread of contagious skin diseases within the community. One of the main challenges faced is the ineffective waste management system and the low awareness among residents regarding the importance of environmental cleanliness. This situation makes environmental issues a matter that requires serious attention. This program aims to demonstrate how communities can be empowered to create a clean, healthy, and comfortable living environment. The research employs a qualitative method with a descriptive approach, collecting data through direct observation and interactive discussions with the community. The results of this empowerment activity reveal that through the Community Service Program (Kuliah Kerja Nyata or KKN), residents are motivated to actively participate in activities such as communal cleaning efforts, making trash bins from local materials, and more organized waste management. The success of this program is supported by the active involvement of the community and backing from the village government, who together play a role in creating positive and sustainable changes at the village level.